Application of pursed-lip breathing to reduce fatigue in hemodialysis patients: A nursing case study - Aneja, Ririn Dwi; Fatrida, Dedi (Lentera Perawat, 2026)
Background: Chronic Kidney Disease (CKD) is a serious global health problem with a rapidly increasing prevalence. The disease is characterized by a progressive and irreversible decline in kidney function. In advanced stages, patients require renal replacement therapy, such as hemodialysis. Fatigue is one of the most common and debilitating symptoms experienced by patients undergoing hemodialysis, negatively affecting daily functioning and quality of life. Objective: This study aimed to describe nursing care for a patient with CKD through the application of pursed-lip breathing to reduce fatigue levels in the Hemodialysis Unit. Methods: This study employed a nursing case study design based on the nursing process. The subject was Mrs. S, a patient with CKD undergoing routine hemodialysis. Fatigue was assessed using the Fatigue Severity Scale (FSS), with an initial score of 52, indicating fatigue. The nursing diagnosis was exhaustion related to physiological conditions (chronic disease: CKD) and long-term treatment (hemodialysis). The nursing intervention consisted of the application of pursed-lip breathing, implemented over four consecutive visits during hemodialysis sessions. Results: The evaluation demonstrated a gradual reduction in fatigue levels. The FSS score decreased from 46 on the first day, to 40 on the second day, 36 on the third day, and reached 30 on the fourth day, indicating no fatigue. In addition, the patient verbalized improved energy recovery, increased strength, reduced feelings of fatigue and lethargy, and improved appetite, consistent with the expected nursing outcomes. Conclusion: The application of pursed-lip breathing as a nursing intervention was associated with a reduction in fatigue levels in a patient undergoing hemodialysis. This technique may be incorporated into routine nursing care to help manage fatigue and support quality of life among patients with CKD. Patients are encouraged to practice pursed-lip breathing regularly, particularly when experiencing fatigue during hemodialysis.